Perancangan Desain Interaksi Modul Pelayanan Kesehatan Masyarakat Pada Aplikasi Malang Sehat Dengan Menggunakan Metode HCD (Human-Centered Design) - Andika Fatimah Az-Zahara; Herman Tolle; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Efforts to improve the quality of public health services continue to be carried out by the Government of Malang. In achieving the increase in access and health services, the Government not only realizes this through improvement of supporting facilities and infrastructure, but also in the form of application-based health services that make it easier for patients to gain access to health services. Today, many countries are innovating to build smart city in order to maximize services for their people, including the Indonesian state. At present the Office of Communication and Information (Kominfo) of Malang City is also working to develop Malang towards smart city. Therefore, to realize this desire one of them can be done by improving the quality of health services in the city of Malang, so it is necessary to design an interaction design for integrated mobile apps based health service applications in order to provide services in an effective, efficient and comfortable way to use the community. This interaction design applies the Human-Centered Design method that focuses on users and stakeholders. At the evaluation stage, testing was conducted with 20 participants using the Remote Usability Testing technique and using the System Usability Scale (SUS) questionnaire, then the test results obtained were the aspect value effectiveness of 99%, efficiency value of 83% and satisfaction value 77.1 which means getting Grade Scale is C value with acceptable level which is high. With this score results get adjective ratings in the 'Good' category.